Wearable Electronics: Biocompatible Cost‐Effective Electrophysiological Monitoring with Oxidation‐Free Cu–Au Core–Shell Nanowire (Adv. Mater. Technol. 12/2020). Issue 12 (9th December 2020) - Kim, Dongkwan; Bang, Junhyuk; Won, Phillip; Kim, Youngtaek; Jung, Jinwook; Lee, Jinwoo; Kwon, Jinhyeong; Lee, Habeom; Hong, Sukjoon; Jeon, Noo Li; Han, Seungyong; Ko, Seung Hwan
Abstract : In article number 2000661, Seungyong Han, Seung Hwan Ko, and co‐workers address the oxidation and biocompatibility issues of Cu nanowires by developing a novel wet chemical synthesis method for the oxidation‐free Cu‐Au core‐shell nanowire based on the prepared Cu nanowire with alkylamine‐mediated synthesis and ligand exchange. Furthermore, high performance wearable electrophysiological monitoring sensors with the Cu‐Au core‐shell nanowire electrode are demonstrated with superior oxidation‐resistance and biocompatibility.